Acoustic measurement of the shear compliance of silicone oil - PŁOWIEC, Ryszard (Archives of Acoustics, 1977)
A method of measurement is described and the results of measurement of the modulus limit shear compliance J∞, of four samples of synthetic oil with different molecular weight compared. Oil properties have been measured acoustically by determining the characteristic shear resistance at a stress frequency of 30 MHz and 450 MHz and in the temperature range from 0°C to –100°C.It was found that the increase of molecular weight has only little influence on the limit of the modulus of shear compliance of the liquid.